Training Final Income Tax Calculation for MSME WITA Jakarta, According to PP 55/2022 - Deden Tarmidi; Waluyo Waluyo; Dwi Asih Surjandari; Noor Hazlina Ahmad (EQUATOR SINAR AKADEMIA, 2023)
Limited Human Resources in MSMEs have an impact on the low compliance of MSME Taxes, so socialization activities need to be carried out by the Government as a Regulator, as well as other parties. This community service activity aims to increase the tax literacy of MSME members of WITA Jakarta. This activity was carried out using socialization, practice, mentoring and evaluation methods, from February 2023 to the end of June 2023 in the form of offline, online and hybrid, with 268 participants in total. From this activity, it is known that many participants do not know the rules related to the latest MSME Income Tax, namely Government Regulation Number 55 of 2022, including how to calculate MSME Income Tax. These results make the basis of input for the Government as a regulator or academics in helping to improve MSME tax literacy, or research in analyzing knowledge of MSME Tax rules.